ANALISIS PROFIL JUDUL PENELITIAN DENGAN RIP LPPM UCY 2022-2027 STUDI PADA FE UCY - Kurnianingsih, Retno (Journal Competency of Business, 2022)
Research activities are one of the tridharma of higher education. For lecturers, this activity is a prerequisite in fulfilling the lecturer's performance load report which is reported every semester, while for students it is a prerequisite for the final project report in fulfilling graduation as a bachelor's degree. The problem is that although the productivity of lecturers' research through student guidance in completing their final assignments has increased, research products that have the potential to be published in national and international journals are still limited. This study aims to determine the profile of research titles for students of the Faculty of Economics, University of Cokroaminoto, Yogyakarta with the research themes in the Research Master Plan (RIP) LPPM UCY 2022-2027. According to the RIP LPPM 2020-2027, the leading themes of research and community service at UCY are set in 5 (five) areas of community life. The field of study is adjusted to the expertise of the study program at UCY. The leading research themes in each field are as follows: 1) Religion Religion: Strengthening Community Religiosity towards the welfare of the nation 2) Economics: Human Resource Management, Financial Management, Marketing and Poverty Alleviation, 3) Law: Strengthening local governance and protection of human rights , 4) Education: Development of IT-based education with Indonesian character 5) Engineering: Disaster Management Management. The results showed that there were 24 titles of student research results with the theme of economics, namely 20 from management study programs and 4 from accounting study programs. Of the 24 themes related to Human Resources there are 2 titles, Financial Management consists of 8 titles, Marketing consists of 14 titles and Poverty Alleviation is not yet available.